Remarks at the Early Childhood Development Event - Kim, Jim Yong (World Bank, Washington, DC, 2019)
Jim Yong Kim, President of the World Bank Group, discussed early childhood development, which covers the physical, cognitive, linguistic, and socio-emotional development of children, starting before birth until they enter primary school.